An Analysis of Mexican Culture “Dia De Los Muertos” in Coco Animation Film - Lestari, Rina; Tiana, Delis Meta (British (Jurnal Bahasa dan Sastra Inggris), 2024)
This research explores the Mexican culture and how animation films can convey foreign traditions, such as "Dia De Los Muertos, or Day of the Dead," through a qualitative descriptive method. Data was collected from visual sources and references to analyze the Mexican culture in the Coco animation film. The study concluded that animated films can effectively introduce foreign cultures to viewers, and the portrayal of death in films does not always have to be associated with gloomy atmospheres. The research aims to provide insight into Mexican culture, Día de los Muertos, allowing viewers to celebrate and respect relatives who have passed away while also learning about the cultural values of the film. The findings suggest that animated films can be a valuable tool for introducing and promoting foreign cultures. Keywords: Mexican culture, Day of the Dead, animation.